The role of calcium in drought stress response induced through antioxidant activity in oil palm (Elaeis guineensis Jacq.) seedlings - Endah NURWAHYUNI; Eka Tarwaca Susila PUTRA (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2021)
Oil palm productivity in Indonesia faces challenges related to drought that occur during the dry season. Calcium is an element that plays a role in determining the response of plant resistance to drought through biochemical activity. This study aims to determine the contribution of calcium in biochemical mechanisms involving various antioxidants. The treatment was arranged in factorial of 3 x 4 in a split-plot design. The first factor was calcium dosage, which consisted of 0 g (control/without calcium), 0.04 g, 0.08 g, and 0.12 g of calcium per plant. The second factor was the intensity of drought stress, referred as the Fraction of Transpirable Soil Water (FTSW) at 1 (control/field capacity), 0.35 (moderate drought), and 0.15 (severe drought) with a week duration of intensity. Calcium was applied in a ring placement on four-month-old seedlings planted in 40 x 40 cm polybags with alfisol soil planting medium and given drought treatment two months later for three weeks. The results showed that calcium could induce plant response to drought through the increase in superoxide dismutase (SOD) activity, the decrease in hydrogen peroxide (H₂O₂) concentration, and the decrease in malondialdehyde (MDA) concentration. The study concluded that calcium is an essential element used to reduce the effects of drought on oil palm seedlings through the change of biochemical activities regulated by enzymatic antioxidants.